2013
DOI: 10.1038/ncomms3713
|View full text |Cite
|
Sign up to set email alerts
|

Hemichordate neurulation and the origin of the neural tube

Abstract: The origin of the body plan of our own phylum, Chordata, is one of the most fascinating questions in evolutionary biology. Yet, after more than a century of debate, the evolutionary origins of the neural tube and notochord remain unclear. Here we examine the development of the collar nerve cord in the hemichordate Balanoglossus simodensis and find shared gene expression patterns between hemichordate and chordate neurulation. Moreover, we show that the dorsal endoderm of the buccal tube and the stomochord expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 36 publications
7
80
0
1
Order By: Relevance
“…The collar cord within the collar region neurulates in a similar way as in Saccoglossus kowalevskii (Fig. 2.8 ) and eventually becomes situated subepidermally (Morgan 1894 ;Miyamoto and Wada 2013 ). From approx.…”
Section: Neurogenesis In Indirect Developing Enteropneustsmentioning
confidence: 92%
See 2 more Smart Citations
“…The collar cord within the collar region neurulates in a similar way as in Saccoglossus kowalevskii (Fig. 2.8 ) and eventually becomes situated subepidermally (Morgan 1894 ;Miyamoto and Wada 2013 ). From approx.…”
Section: Neurogenesis In Indirect Developing Enteropneustsmentioning
confidence: 92%
“…More condensed areas are present in the trunk region, where they constitute a dorsal and a ventral median longitudinal nerve cord, respectively (Bullock 1946 ;Knight-Jones 1952 ). Furthermore, the dorsal nerve cord continues anteriorly into the collar region to form the subepidermal, hollow collar cord that is reminiscent of the neural tube present in chordates (Morgan 1894 ;Kaul and Stach 2010 ;Miyamoto and Wada 2013 ). The collar cord links to the basiepidermal plexus at the base of the proboscis, that is, the proboscis stem.…”
Section: Enteropneustamentioning
confidence: 97%
See 1 more Smart Citation
“…However, several studies demonstrate the formation of a dorsal, neural tube-like structure in acorn worm adults [65][66][67], which is reminiscent of dorsal, neural tube formation of chordate embryos. It should be noted that the inversion hypothesis cannot necessarily explain the occurrence of chordate-specific structures or the notochord [18,55].…”
Section: (C) the Inversion Hypothesismentioning
confidence: 99%
“…In another gene expression study, Cunningham & Casey [37] similarly proposed that a CNS was present and was composed of the trunk ventral nerve cord, trunk dorsal nerve cord and collar cord (figure 3f ); they likewise found that the peripheral nervous system included relatively few neurons at advanced developmental stages. Finally, Miyamoto & Wada [46] focused on the Hedgehog gene in developing enteropneusts and demonstrated its endodermal expression in the stomochord and roof of the buccal cavity, while the dorsal ectoderm was differentiating and invaginating to form the collar nerve cord. The situation was reminiscent of what happens in neurulating embryos of vertebrates when Hedgehog signalling from the notochord plays a key role in the genesis of the neural tube.…”
Section: Second Revived Enteropneust Scenariorepudiating Bateson Againmentioning
confidence: 99%